Manejo da diversidade genética de milho como estratégia para a conservação da agrobiodiversidade no Norte de Minas Gerais - Natalia Carolina de Almeida Silva (2011)
This study aimed to understand the management of genetic diversity of maize in communities of family farmers in the north of Minas Gerais from two components: 1) diagnosis of the informal system of management and, 2) local tests of maize varieties. Field surveys were conducted from November 2008 to June of 2010. For the diagnosis of the informal system of management of the genetic diversity of maize, they were interviewed through semi-structured questionnaire. The interviews were not conducted at a specific time of the survey, but in addition to activities related to local tests of maize varieties. Other data collection and information took place during the meetings with each group of farmers, both made in discussions at meetings as in moments of collective work and evaluation in the field. In addition to the records made from the experience of these moments, it was also made the use of photographic records. In the first stage of monitoring and evaluation realized in 2008 and 2009, nine trials were installed at the following locations: the first was implanted in AEFA in Montes Claros, the others in the communities of Sambaíba, Barra do Tamboril and Pau dÓleo in Januária, Tapera settlement, in Riacho dos Machados, in the area of STR of Varzelândia, in Varzelândia, in the Itapicuru community in Porteirinha and the Vargens/Xakriabá Village in São João das Missões. In the second phase, conducted in 2009 and 2010, the trials were installed at the same sites, except Varzelândia and Porteirinha, which were installed in the Vereda community and Mocambo da Onça, respectively. Moreover, the work was expanded to three more locations: Americana settlement in Grão Mogol, Jardim community in Rio Pardo de Minas and Vale do Guará settlement in Vargem Grande do Rio Pardo. Unlike the stage 2008-2009, in the stage of 2009-2010, it was adopted during the visual assessment of the spikes in each group picked a few varieties from their own selection criteria, preferences and needs. It was found that the family farmers participating in the research still keep in use a considerable amount of maize varieties. This has been guaranteed by constant experimentation, by keeping the dynamics of informal networks for exchange of seeds and knowledge. The performance of the tests allowed that the participating farmers know other varieties, disseminate those that grow, in the addition to enabling the exchange of seeds and the increase of the diversity of maize in its agroecosystems, besides they contribute to the identification of important genetic sources for the different agroecological systems proving the productive potential of local varieties. Farming communities have demonstrated their ability to participle with quality initiatives and the effectiveness of testing being necessary, thus, to enhance and integrate, in fact, their knowledge that are the result of their practical and reflective perform. Initiatives of the Rede Norte Mineira of the Agrobiodiversidade have reflected positively on informal networks studies, mainly by providing participation and management of agrobiodiversity.